Association of TGF-β1 -509 C > T (rs1800469) polymorphism with bone marrow failure severity in Fanconi anemia subjects - Chavan, Niranjan Sheshrao; George, Merin; Dhangar, Somprakash; Hadkar, Shraddha; Ghatanatti, Jagadeeshwar; Rajendran, Aruna; Nemani, Sandeep; Mudaliar, Sangeeta; Manglani, Mamta; kini, Pranoti; Vundinti, Babu Rao (Molecular biology reports, 2025)
Background Fanconi anemia (FA) is a rare inherited genetic disorder marked by defective DNA repair mechanisms, bone marrow failure (BMF), and increased cancer susceptibility. Cytokines, specifically TGF-β are reported to be critical in FA pathophysiology, and their increased level leads to exacerbated BMF; however, the effect of genetic variability on TGF-β expression and clinical outcome remains poorly understood. This study investigates the impact of TGF-β1 -509 C > T polymorphism (rs1800469) on TGF-β expression. Methods The study was carried out on 61 confirmed diagnosed FA subjects, using chromosomal breakage studies and molecular analysis. Genotyping was performed via Sanger sequencing, and TGF-β1 quantification was carried out using ELISA and qRT-PCR. Chi-square or Fisher’s exact tests, and ANOVA (or Kruskal-Wallis tests in non-normal distributions) were performed to calculate the statistical significance. Results All 61 FA subjects showed a high frequency of chromosomal breaks and mutations in FA complementation groups. The genotyping of TGF-β1 -509 C > T polymorphism (rs1800469) revealed the following genotype frequencies: CC (41%), CT (44.2%) and TT (14.8%). The allelic frequency was C = 0.63 for the major allele and T = 0.37 for the minor allele. The TGF-β1 expression was genotype dependent. Individuals with the CC genotype showed maximum levels of TGF-β1 expression, while CT heterozygotes showed intermediate expression, and the TT homozygotes showed significantly lower levels of mRNA and protein expression. Notably, the TT genotype, associated with reduced TGF-β1 expression, correlated with improved haematological parameters, including higher haemoglobin and neutrophil count, suggesting a protective role against severe BMF. Conclusions This study suggests rs1800469 polymorphism as a critical modifier of TGF-β1 expression in FA, and suggests that the TT genotype may confer a protective advantage by reducing the severity of bone marrow failure.